A simple, sensitive, high-resolution, customized, reverse phase ultra-high performance liquid chromatographic method for related substances of a therapeutic peptide (bivalirudin trifluoroacetate) using the quality by design approach. Issue 3 (17th December 2019) - Kumar, K. Y. Kiran; Dama, Venugopala Rao; Suchitra, Ch.; Maringanti, Thirumala Chary
Abstract : Among all chemical sameness characterization tests of Therapeutic Peptides (TPs), one of the most significant and challenging aspects is to demonstrate comparable impurity profiles (both qualitative & quantitative) between a generic product and reference listed drug (RLD). Abstract : Among all chemical sameness characterization tests of Therapeutic Peptides (TPs), one of the most significant and challenging aspects is to demonstrate comparable impurity profiles (both qualitative & quantitative) between a generic product and reference listed drug (RLD). Though multiple state of the art orthogonal analytical methods are being used for the identification and quantification of related impurities in TPs, it is important that the developed methods are simple, selective, and sensitive, and can be easily implementable in quality control laboratories. The current published chromatographic (HPLC or UHPLC) methods for the quantification of related substances in TPs rarely use non-mass spectrometry compatible ion pairing reagents (NMS-IPRs) in the mobile phase composition over mass spectrometry compatible ion pairing reagents (MS-IPRs), due to their compatibility issues with high-resolution mass-based detection methods. We hypothesize that achieving mixed mode stationary phase characteristics using hydrophobic NMS-IPRs such as sodium 1-butanesulfonate, at concentrations <10 mM in the diethanolammonium phosphate buffer (pH 2.9) on a C-18 stationary phase, would be able to resolve critical impurities such as Penta-Gly, D-Asn, and Tri-Gly using the single UHPLC method, and is also selective to all other related impurities of bivalirudin (BIV) cited in the literature. Furthermore, customization of column dimensions (300 mm × 2.1 mm × 1.8 μm) helped in achieving a resolution (Rs) > 2.0 between Penta-Gly & BIV, and a peak to valley ratio (Hp/Hv) > 4.0 between BIV & D-Asn and D-Asn & Tri-Gly impurities. The developed method is sensitive (LOQ ∼ 0.05% with respect to analyte concentration), precise, accurate, and linear in the range of 1 μg mL −1 to 2500 μg mL −1 . This method is rugged, robust, and easily implementable in quality control laboratories for monitoring the related impurities of bivalirudin.